2008
DOI: 10.1590/s0103-90162008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Carrot seed germination and vigor in response to temperature and umbel orders

Abstract: Several factors may influence carrot (Daucus carota L.) crop establishment. High temperatures (35 -40°C), for instance, may delay or inhibit carrot seed germination in the field and so compromise the stand establishment. Carrot seeds from superior umbel orders usually have better physiological quality than those of lower umbel orders. These seeds from superior umbel orders may also show a better performance in adverse conditions. In addition, seeds from different ages show differences in vigor, which affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…Emergence rate revealed that the time required for the seeds to express their maximum capacity for germination was five days in seeds from the primary umbels, and seven days in seeds from the tertiary umbels. This result agrees with Pereira, Nascimento and Vieira (2008), who stated that seeds from the primary umbels display superior physiological quality when compared to the remaining orders. Biochemical and physiological analysis in carrot seeds from different orders of umbels In analysis of the thousand-seed weight, 0.180; 1,162 and 1,150 g were obtained for the primary, secondary and tertiary umbels respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Emergence rate revealed that the time required for the seeds to express their maximum capacity for germination was five days in seeds from the primary umbels, and seven days in seeds from the tertiary umbels. This result agrees with Pereira, Nascimento and Vieira (2008), who stated that seeds from the primary umbels display superior physiological quality when compared to the remaining orders. Biochemical and physiological analysis in carrot seeds from different orders of umbels In analysis of the thousand-seed weight, 0.180; 1,162 and 1,150 g were obtained for the primary, secondary and tertiary umbels respectively.…”
Section: Resultssupporting
confidence: 92%
“…High temperatures have a major influence on carrot seed germination, with some cultivars not germinating and others displaying dramatically reduced germination under such conditions PEREIRA;VIEIRA, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicating that most of genotypes with more test weight and size of seed bear better germination percentage, however, this is not true in respect of each genotype. Similarly, Pereira et al, (2008) mentioned that increase in seed germination and development is owing to the higher seed size, weight and density. Seeds with fully mature embryos and high amounts of food reserves are potentially the most germinative and vigorous ones (Carvalho and Nakagawa, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Seed vigor can be evaluated by the physiological, biochemical and stress tolerance tests which are commonly used for carrot and other species (Pereira et al, 2008;Chiquito et al, 2012;Kikuti and Marcos Filho, 2013). Computerized image analysis of seedlings has been used for seed vigor evaluation in several species; these are non-destructive methods and can provide objective information in a short period of time with less human interference (McCormac et al, 1990;Marcos Filho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%